Catalyst for synthesizing methane by reducing carbon dioxide through electro-catalysis as well as preparation method and application of catalyst
Through the bimetallic catalyst formed by copper and silver, the synergistic effect and special morphology improve the catalytic activity, solving the problems of poor stability and low yield of existing electrocatalytic carbon dioxide reduction catalysts, and achieving the effect of efficient methane synthesis.
Patent Information
- Application Number
- CN202411684632.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
AI Technical Summary
Existing electrocatalytic carbon dioxide reduction catalysts have problems such as poor stability, low yield and serious side reactions, resulting in poor selectivity of single product of methane.
A bimetallic catalyst formed by copper and silver is used to improve catalyst activity through the synergistic effect between the catalytic components and provide more catalytic active sites through special morphology. The catalyst is prepared by ultrasonic dispersion, hydrothermal reaction and other steps. Glucose and hexadecamine are used as reducing agents and blocking agents to conduct hydrothermal reactions under different temperatures and time conditions respectively.
The high-efficiency electrocatalytic carbon dioxide reduction synthesized methane has the advantages of simple synthesis process, strong electrocatalytic activity and good stability, which significantly improves the selectivity and yield of methane.
Smart Images

Figure CN119465257A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a catalyst for electrocatalytic carbon dioxide reduction to methane synthesis, and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Carbon dioxide is a substance that is ubiquitous in nature and participates in the carbon cycle in nature. However, in recent years, due to the large amount of carbon dioxide emitted by humans into the atmosphere, its concentration has continued to rise, resulting in the greenhouse effect, which has caused a lot of additional heat to be captured by the earth. The global temperature has continued to rise, bringing about a series of environmental problems such as global warming and sea level rise. In order to reduce the damage to nature and achieve economic feasibility at the same time, humans need to explore industrial routes for the resource utilization of carbon dioxide. Carbon dioxide capture, utilization and storage (CCUS) technology is one of the main ways to achieve a low-carbon economy. Among them, converting carbon dioxide into valuable fuels or chemicals can better achieve the dual carbon goals and is a very promising strategy. Common carbon dioxide conversion methods include chemical reduction, photocatalytic reduction, biotechnology conversion and electrocatalytic reduction. Among them, electrocatalytic reduction of carbon dioxide is one of the most promising carbon dioxide reduction strategies at present because of its high energy efficiency and relatively mild reaction conditions.
[0004] There are many factors that affect the carbon dioxide reduction reaction, among which the catalyst is one of the most important factors. Among the many metal-based catalysts, copper has very unique properties and is the only catalyst that can produce high value-added products such as methane and ethylene. However, it is precisely because of the large number of products of copper catalysts that the selectivity of its single product is poor, which increases the cost of product processing and separation. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a catalyst for electrocatalytic carbon dioxide reduction to methane synthesis, and a preparation method and application thereof. By forming a bimetallic catalyst with copper and silver, the catalyst activity can be improved through the synergistic effect between the catalytic components, and its special morphology provides more catalytic active sites, solving the problems of poor catalyst stability, low yield, and serious side reactions in the existing electrocatalytic reduction process, and realizing efficient electrocatalytic carbon dioxide reduction to methane synthesis, with the advantages of simple synthesis process, strong electrocatalytic activity, good stability, etc.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a catalyst for electrocatalytic reduction of carbon dioxide to methane, comprising the following steps:
[0008] Add soluble copper salt, hexadecylamine and glucose into water, and disperse by ultrasonic to obtain a mixed solution;
[0009] The mixed solution is subjected to a first hydrothermal reaction at 110-130° C., and then mixed with a mixed solution of silver salt and imidazole, and then subjected to a second hydrothermal reaction at 45-55° C. The hydrothermal reaction time is 20-30 minutes;
[0010] After the reaction is completed, the solid and liquid are separated, and the solid is washed and dried.
[0011] Among them, the first hydrothermal reaction uses glucose as a reducing agent to reduce the divalent copper ions in the soluble copper salt to zero-valent copper metal. Hexadecylamine is used as a capping agent to adjust the surface energy and growth rate of different crystal faces and affect the final morphology of the nanomaterial. The second hydrothermal reaction is an electrical replacement method, which uses the potential difference between metallic copper and silver ions in the aqueous solution to make the silver ions spontaneously reduced to a metallic state. Imidazole is a capping agent, which is mainly used to control the reaction rate.
[0012] In some embodiments, the soluble copper salt is copper chloride, copper nitrate, or copper sulfate.
[0013] In some embodiments, the mass ratio of soluble copper salt, hexadecylamine, glucose, silver salt and imidazole is 0.8-1.5:8-10:2-4:0.4-0.6:0.3-0.5.
[0014] Preferably, the mass ratio of soluble copper salt, hexadecylamine, glucose, silver salt and imidazole is 1-1.3:8.5-9.5:2-3:0.4-0.5:0.3-0.4.
[0015] In some embodiments, the first hydrothermal reaction takes 7-10 hours.
[0016] In some embodiments, the washing liquid used for washing the solid is a mixture of n-hexane and ethanol, in which the volume ratio of n-hexane to ethanol is 1:0.8-1.2, preferably 1:1; n-hexane, as a typical non-polar solvent, has an excellent effect on removing hexadecylamine in the mixture; ethanol is used to enhance the solubility of hydrophilic species in the mixture.
[0017] In a second aspect, the present invention provides a catalyst for electrocatalytic carbon dioxide reduction to methane, which is prepared by the preparation method.
[0018] In a third aspect, the present invention provides application of the catalyst in electrocatalytic carbon dioxide reduction.
[0019] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0020] (1) The preparation method is simple. The preparation method of the metallic silver-loaded copper nanowires provided by the present invention is simple, the raw materials are easily available, there are no toxic or harmful raw materials and by-products, the synthesis scale is easy to scale up, and it is conducive to industrial production;
[0021] (2) Good catalytic performance. The metallic silver-supported copper nanowire catalyst provided by the present invention achieves high product selectivity and catalytic activity in the process of electrocatalytic carbon dioxide reduction to methane, which is of great significance for the industrial promotion of electrocatalytic carbon dioxide reduction to methane.
[0022] (3) Strong scalability. The method for preparing metallic silver-loaded copper nanowires provided by the present invention can prepare other types of copper-based catalysts by adjusting the metal loading amount, metal type, reduction conditions, etc., and can be applied to a variety of different catalytic scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 is a transmission electron microscope image of metallic silver-loaded copper nanowires prepared in Example 3 of the present invention;
[0025] Figure 2 is a transmission electron microscope image of the copper nanowires prepared in Example 2 of the present invention;
[0026] Figure 3 is an energy spectrum diagram of metallic silver-loaded copper nanowires prepared in an embodiment of the present invention;
[0027] Figure 4 is an X-ray diffraction spectrum of the copper nanowires and the metallic silver-loaded copper nanowires prepared in the embodiments of the present invention;
[0028] Figure 5 is a Faraday efficiency diagram of various products of the metallic silver-loaded copper nanowires prepared in an embodiment of the present invention at different potentials;
[0029] Figure 6 3 is a Faraday efficiency diagram of various products of the copper nanowires prepared in an embodiment of the present invention at different potentials. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] The present invention will be further described below in conjunction with the embodiments.
[0032] Example 1
[0033] 1.1 g of copper chloride dihydrate, 9 g of hexadecylamine and 2.5 g of glucose were added to 500 mL of deionized water and ultrasonically treated in an ultrasonic cleaner for 1 hour. The reaction system was then transferred to a hydrothermal kettle, heated to 120 ° C for 8 hours, and then taken out and cooled overnight. 0.486 g of silver acetate and 0.335 g of imidazole were mixed in 400 mL of deionized water, 50 mL of the mixture was added to the copper nanowire solution, and the reaction system was placed in a 50 ° C oil pan and heated for 25 minutes. The product was washed with a 1:1 mixture of n-hexane and ethanol, and collected by centrifugation at a speed of 10000 rpm for 5 minutes, and repeated 5-6 times. After collection, the product was placed in a vacuum and dried to obtain metallic silver-loaded copper nanowires.
[0034] Example 2
[0035] Add 1.1 g of copper chloride dihydrate, 9 g of hexadecylamine and 2.5 g of glucose to 500 mL of deionized water and ultrasonically treat in an ultrasonic cleaner for 1 hour. Then transfer the reaction system to a hydrothermal kettle, heat to 120 ° C and heat for 8 hours. After completion, take it out and cool overnight. Wash the product with a 1:1 mixture of n-hexane and ethanol, collect it by centrifugation at 10000 rpm for 5 minutes, and repeat 5-6 times. After collection, dry the product in a vacuum to obtain copper nanowires.
[0036] Example 3
[0037] 1.1 g of copper chloride dihydrate, 9 g of hexadecylamine and 2.5 g of glucose were added to 500 mL of deionized water and ultrasonically treated in an ultrasonic cleaner for 1 hour. The reaction system was then transferred to a hydrothermal kettle, heated to 120 ° C for 8 hours, and then taken out and cooled overnight. 0.486 g of silver acetate and 0.335 g of imidazole were mixed in 400 mL of deionized water, 50 mL of the mixture was added to the copper nanowire solution, and the reaction system was placed in a 50 ° C oil pan and heated for 25 minutes. The product was washed with a 1:1 mixture of n-hexane and ethanol, and collected by centrifugation at a speed of 10000 rpm for 5 minutes, and repeated 5-6 times. After collection, the product was placed in a vacuum and dried to obtain metallic silver-loaded copper nanowires.
[0038] The microstructure of the obtained metallic silver-loaded copper nanowires was characterized by transmission electron microscopy. Figure 1 As shown in Figure 1, metallic silver is attached to the surface of the copper nanowire in the form of nanoparticles. The microstructure of the obtained copper nanowire was characterized by scanning electron microscopy, as shown in Figure 1. Figure 2 As shown in Figure 2, it can be seen that the nanowire structure has not changed significantly during the synthesis process. The distribution of elements on the surface of the material was detected using an energy spectrometer, such as Figure 3 As shown in Figure 2, it is confirmed that the main body of the nanowire is copper and silver is attached to the nanowire in the form of particles. The copper-silver nanowire lattice was characterized using XRD technology, as shown in Figure 2. Figure 4 As shown, it was found that in addition to the three crystal planes of Cu(111), Cu(200) and Cu(220) of copper nanowires, there are also multiple silver crystal planes such as Ag(111), Ag(200) and Ag(220).
[0039] Example 4
[0040] 1.1 g of copper chloride dihydrate, 9 g of hexadecylamine and 2.5 g of glucose were added to 500 mL of deionized water and ultrasonically treated in an ultrasonic cleaner for 1 hour. The reaction system was then transferred to a hydrothermal kettle, heated to 120 ° C for 8 hours, and then taken out and cooled overnight. 0.486 g of silver acetate and 0.335 g of imidazole were mixed in 400 mL of deionized water, 50 mL of the mixture was added to the copper nanowire solution, and the reaction system was placed in a 50 ° C oil pan and heated for 25 minutes. The product was washed with a 1:1 mixture of n-hexane and ethanol, and collected by centrifugation at a speed of 10000 rpm for 5 minutes, and repeated 5-6 times. After collection, the product was placed in a vacuum and dried to obtain metallic silver-loaded copper nanowires.
[0041] 10 mg of silver-loaded copper nanowires were dispersed in a mixed solution of 100 μL Nafion and 2400 μL isopropanol, and then sprayed on carbon paper to make an electrode. The performance was evaluated using an H-type electrolytic cell system. Under the conditions of 0.1 mol / L potassium bicarbonate electrolyte and 30 ml / min of carbon dioxide flow, different overpotentials were applied to the cathode, and the Faraday efficiency (FE) of different products at the corresponding current density was measured, such as Figure 5 The results show that at high potential (about -1.7 V vs. RHE), the silver-loaded copper nanowires achieve good selectivity for methane.
[0042] Example 5
[0043] Add 1.1 g of copper chloride dihydrate, 9 g of hexadecylamine and 2.5 g of glucose to 500 mL of deionized water and ultrasonically treat in an ultrasonic cleaner for 1 hour. Then transfer the reaction system to a hydrothermal kettle, heat to 120 ° C and heat for 8 hours. After completion, take it out and cool overnight. Wash the product with a 1:1 mixture of n-hexane and ethanol, collect it by centrifugation at 10000 rpm for 5 minutes, and repeat 5-6 times. After collection, dry the product in a vacuum to obtain copper nanowires.
[0044] 10 mg of copper nanowires were dispersed in a mixed solution of 100 μL Nafion and 2400 μL isopropanol, and then sprayed on carbon paper to make an electrode. The performance was evaluated using an H-type electrolytic cell system. Under the conditions of 0.1 mol / L potassium bicarbonate electrolyte and continuous flow of 30 ml / min of carbon dioxide, different overpotentials were applied to the cathode, and the Faraday efficiency (FE) of different products at the corresponding current density was measured, such as Figure 6 The results show that compared with the silver-loaded copper nanowires, the selectivity of the copper nanowires for various carbon products at different potentials decreased, proving that the loaded silver can effectively improve the selectivity of the catalyst for carbon products.
[0045] Experimental results
[0046] Through the working condition exploration and performance comparison of the above examples, the silver-loaded copper nanowires effectively improve the selectivity and reaction activity of the catalyst to the product through the synergistic effect between metals and metal oxides. At the same time, its simple and universal synthesis method makes it easy to change parameters such as the loaded metal precursor and the loading amount, and it is easy to scale up the preparation scale, which has a good prospect for industrial promotion.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for electrocatalytic reduction of carbon dioxide to methane, characterized in that: The steps include: Add soluble copper salt, hexadecylamine and glucose into water, and disperse by ultrasonic to obtain a mixed solution; The mixed solution is subjected to a first hydrothermal reaction at 110-130° C., then mixed with a mixed solution of silver salt and imidazole, and then subjected to a second hydrothermal reaction at 45-55° C. The hydrothermal reaction time is 20-30 min; After the reaction is completed, the solid and liquid are separated, and the solid is washed and dried.
2. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 1, characterized in that: The soluble copper salt is copper chloride, copper nitrate or copper sulfate.
3. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 1, characterized in that: The mass ratio of soluble copper salt, hexadecylamine, glucose, silver salt and imidazole is 0.8-1.5:8-10:2-4:0.4-0.6:0.3-0.
5.
4. The method for preparing the catalyst for electrocatalytic carbon dioxide reduction to methane synthesis according to claim 3, characterized in that: The mass ratio of soluble copper salt, hexadecylamine, glucose, silver salt and imidazole is 1-1.3:8.5-9.5:2-3:0.4-0.5:0.3-0.
4.
5. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 1, characterized in that: The first hydrothermal reaction time is 7-10h.
6. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 5, characterized in that: The first hydrothermal reaction time is 7-9h.
7. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 1, characterized in that: The washing liquid used for washing the solid is a mixture of n-hexane and ethanol, and the volume ratio of n-hexane to ethanol in the mixture is 1:0.8-1.
2.
8. The method for preparing the catalyst for electrocatalytic reduction of carbon dioxide to methane according to claim 7, characterized in that: The volume ratio of n-hexane to ethanol in the mixed solution is 1:
1.
9. A catalyst for electrocatalytic reduction of carbon dioxide to methane, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the catalyst according to claim 9 in electrocatalytic carbon dioxide reduction.
Citation Information
Cited By
Ag-Cu composite metal aerogel and preparation method and application thereof
CN120624860A